Factors Associated with Cellulitis of Lower Limbs among Patients Attending Madina Hospital in Mogadishu, Somalia - Mohamed, Mohamud Yusuf; Aydemir, Muhammet Ali; Ozsoy, Mehmet Sait; Hassan, Mohamed Yusuf; Fiqi, Abdurrahman Osman; Eren, Tunc; Alimoglu, Orhan (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Cellulitis is an acute bacterial infection causing inflammation of the deep dermisand surrounding subcutaneous tissue without an abscess or purulent discharge. The risk factorsof cellulitis can be classified into general and local factors. General risk factors include obesity,diabetes mellitus, and history of cellulitis, immunosuppression, lymphedema and peripheralvascular disease while local risk factors include neglected wounds, toe-web intertrigo and legulcers. Objective: To evaluate factors associated with cellulitis of lower limbs among patientsattending Madina hospital in Mogadishu Somalia. Methods: The study design was cross-sectionalstudy design which involved use of quantitative measures associated with cellulitis of lower limbs.Results: A total of 133 patients were evaluated and their data was analyzed. Of them, 78 (58.65%)were male, 55 (41.35%) were female and 63 (47.37%) were between 51-60 years of age. It wasobserved that 38 (28.57%) of the patients were overweight. There was a history of diabetes mellitusin 55 (41.35%) and heart disease in 33 (17.29%) patients, 66 (49.62%) of the patients had a lowincomelevel. In the study, 76 (57.14%) cellulitis developed on the right leg and 57 (42.86%)cellulitis developed on the left leg. In terms of educational level, 74 (55.64%) of the patients wereilliterate and 97 (72.93%) of the patients lived in urban areas. Conclusion: Cellulitis is an acutebacterial infection of the dermis and subcutaneous tissue. Diabetes mellitus, overweight, lowincomelevel are the most risk factors for cellulitis. International Journal of Human and Health Sciences Vol. 08 No. 04 Oct’24 Page: 315-320